Reduction of Kcnt1 is therapeutic in mouse models of SCN1A and SCN8A epilepsy - Hill, Sophie F.; Jafar-Nejad, Paymaan; Rigo, Frank; Meisler, Miriam H. (Frontiers in Neuroscience, 2023)
Developmental and epileptic encephalopathies (DEEs) are severe seizure disorders with inadequate treatment options. Gain-or loss-of-function mutations of neuronal ion channel genes, including potassium channels and voltage-gated sodium channels, are common causes of DEE. We previously demonstrated that reduced expression of the sodium channel gene Scn8a is therapeutic in mouse models of sodium and potassium channel mutations. In the current study, we tested whether reducing expression of the potassium channel gene Kcnt1 would be therapeutic in mice with mutation of the sodium channel genes Scn1a or Scn8a. A Kcnt1 antisense oligonucleotide (ASO) prolonged survival of both Scn1a and Scn8a mutant mice, suggesting a modulatory effect for KCNT1 on the balance between excitation and inhibition. The cation channel blocker quinidine was not effective in prolonging survival of the Scn8a mutant. Our results implicate KCNT1 as a therapeutic target for treatment of SCN1A and SCN8A epilepsy.